IMPROVING RELATIONSHIPS TO ENHANCE CUSTOMER LOYALTY AT WARUNK BARBARKU RESTAURANT - Syahputra, Norman Adi; Permatasari, Berlintina (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The aim of this research is to assess the significance of trust in customer relationships in determining customer satisfaction and to gauge the level of success of Warunk Barbarku Restaurant in fostering customer loyalty. Subsequently, further research is conducted to examine the enhancement of the relationship towards loyalty among the customers of Warunk Barbarku Restaurant. This qualitative research employs an in-depth interview method with purposive sampling, involving a total of 10 carefully selected customers based on strict criteria as respondents, and focuses on a relationship-based approach. Finally, the results of the interviews show that customers perceive comfort in the relationship, trust, and satisfaction as key factors influencing their loyalty to Warunk Barbarku Restaurant. Keywords: Customer Relationship; Marketing; Customer Intimacy; Loyalty; Restaurant